Primary umbilical endometriosis: clinical aspects and long-term follow-up of five cases - MengHui Li; KunNing Zhang; ChongDong Liu (Journal of International Medical Research)
Umbilical endometriosis (UE) is a rare condition. We have documented the clinical characteristics, management strategies, and follow-up results for five cases treated at our hospital between 1998 and 2020, with patients aged between 31 and 44 years. Patients typically presented with umbilical swelling. In all cases, surgical removal was effective and no complications were reported. Two patients had concurrent ovarian endometriosis and one adenomyosis. No umbilical recurrence was recorded during follow-up. We believe that these findings offer valuable insights for the management of this patient population. Clinical management strategies for this disease should be tailored to each patient and carried out collaboratively by both general and gynaecological physicians.